2015
DOI: 10.1002/wcc.372
|View full text |Cite
|
Sign up to set email alerts
|

Decadal changes in radiative fluxes at land and ocean surfaces and their relevance for global warming

Abstract: Anthropogenic interference with climate occurs primarily through modification of radiative fluxes in the climate system. Increasing releases of greenhouse gases into the atmosphere lead to an enhancement of thermal radiation from the atmosphere to the surface by presently about 2 W m−2 per decade, thereby causing global warming. Yet not only thermal radiation undergoes substantial decadal changes at the Earth surface, but also incident solar radiation (SSR), often in line with changes in aerosol emissions. Lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
148
0
5

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(180 citation statements)
references
References 122 publications
9
148
0
5
Order By: Relevance
“…Of these, 638 have sunshine duration records that cover at least 85 % of the whole measurement period since the 1950s. Moreover, it has been demonstrated that sunshine duration is able to capture variations in cloudiness and, to a lesser extent, the signal from aerosol concentrations (Sanchez-Lorenzo et al, 2009;Wang et al, 2012c;Sanchez-Romero et al, 2014Li et al, 2016;Wild, 2016). Similar to the surface solar radiation trends, a transition from decreasing to leveling off was also noted in the sunshine duration trends in China around 1990 (Wang et al, 2013.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Of these, 638 have sunshine duration records that cover at least 85 % of the whole measurement period since the 1950s. Moreover, it has been demonstrated that sunshine duration is able to capture variations in cloudiness and, to a lesser extent, the signal from aerosol concentrations (Sanchez-Lorenzo et al, 2009;Wang et al, 2012c;Sanchez-Romero et al, 2014Li et al, 2016;Wild, 2016). Similar to the surface solar radiation trends, a transition from decreasing to leveling off was also noted in the sunshine duration trends in China around 1990 (Wang et al, 2013.…”
Section: Introductionmentioning
confidence: 74%
“…Subsequently, a transition from a decrease to an increase in surface solar radiation occurred in many regions of the world from the mid-1980s on the order of 1 to 4 W m −2 (Wild et al, 2005;Wild, 2012Wild, , 2016. These phenomena are popularly known as "global dimming and brightening", where "global" originally referred to "global radiation" as a synonym for surface solar radiation but is often interpreted in terms of a global-scale dimension (Wild, 2009(Wild, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…From the longest 25 records covering 353 years, a mean increase in downward longwave radiation of +2.0 Wm -2 per decade since the early 1990s is obtained, in line with our expectations from an increasing greenhouse effect. Thereby, three quarter of the BSRN sites show positive trends (19 sites in total, 9 of them significant), while one quarter show negative trends (6 sites, 3 significant) 3 . The change in downward longwave radiation quantitatively agrees well with the respective change calculated by the latest generation of global climate models (CMIP5).…”
Section: Longwave Changesmentioning
confidence: 90%
“…This applies not only for the longwave radiation as expected from the increasing greenhouse effect, but also for the amount of shortwave radiation that reaches the Earth surface [1][2][3] . Many of the historic records of surface shortwave radiation show substantial declines from the 1950s to the 1980s, known as "global dimming" 4 , and a partial recovery thereafter, known as "brightening" 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Interest on the 7 solar radiation changes has also been raised after the development of solar energy applications, 8 which are continuously growing in number over the recent years. Changes in SSR have been 9 recorded over the last century and can be caused either by natural events such as volcanic eruptions 10 or human-related activities, mainly in polluted regions (Wild, 2016). At larger scales (thousands of 11 years) changes in SSR, might have been caused by changes in the Earth's orbit and Sun solar output 12 (Lean, 1997;Ohmura, 2006).…”
mentioning
confidence: 99%